ПІДВИЩЕННЯ ЕНЕРГЕТИЧНОЇ ЕФЕКТИВНОСТІ РЕГУЛЬОВАНОГО ЕЛЕКТРОПРИВОДУ ОДНОЦИЛІНДРОВОГО ПОРШНЕВОГО КОМПРЕСОРА - Шуруб, Ю.В.; Попович, О.М.; Бібік, О.В. (Інститут електродинаміки НАН України, Київ, 2024)
The peculiarities of the operation of closed systems of adjustable electric drives of single-cylinder reciprocating compressors due to the presence of a non-linear dependence between the motor load torque and the angular movement of its rotor are considered. The method of synthesis of the regulator of the amplitude of the supply voltage of an induction motor of such an electric drive at a fixed value of the supply frequency is proposed. According to the results of research, it was found that the effect of increasing energy efficiency (reducing the difference in efficiency for constant and periodic loads) due to the use of a voltage regulator increases with a decrease in the power supply frequency. It is shown that the optimization of the transmission coefficient of the voltage regulator of electric drives with a non-linear dependence between the motor load torque and the angular movement is expedient to be carried out according to the criterion of maximum efficiency. References 25, figures 10, table 1.